Factors that influence worker behavior towards occupational safety and health using the SEM-PLS method at PT. Industri Kapal Indonesia (Persero) Makassar - Herdianzah, Yan; Wahyuni P, A. Dwi; Ahmad, Arfandi; Chantika, Aulia Marista Dewi; Saleh, Anis; Fole, Asrul; Safutra, Nur Ihwan (OPSI, 2024)
PT. IKI is a shipbuilding company owned by the Indonesian government which carries out several industrial activities such as ship building, repair and docking. The results of initial observations found that there were still workers in the production division who experienced work accidents and occupational diseases. In this research, it is very important to analyze the factors that influence the behavior of production division workers to find out what suggestions for improvements are appropriate in overcoming problems with production division workers. This research employs the SEM-PLS method to investigate the impact of knowledge factors (X1), attitudes (X2), and the availability of facilities (X3) on the occupational safety and health of production division workers. It aims to provide valuable insights for enhancing workplace safety by identifying factors that positively influence these outcomes. The findings of this study reveal a significant correlation between the availability of facilities (X3) and occupational safety and health, as evidenced by a p-value of 0.000, which is less than the predetermined significance level of 0.05. Based on these results, recommendations for improvement can be proposed. The company is advised to uphold and enhance the implementation of Standard Operational Procedures about Occupational Safety and Health (K3) while also ensuring the continuous provision of comprehensive Personal Protective Equipment (PPE) for all employees